Goal-directed behavior - Aarts, Henk.; Elliot, Andrew J. (New York, NY : Psychology Press, 2012)
This volume presents chapters from internationally renowned scholars in the area of goals and social behavior. The book is organized around a series of topics that are of critical importance to understanding the social-cognitive aspects of goal-directed behavior. In each chapter, the authors offer an introduction to past research on a specific topic and combine this with a presentation of their own empirical work to provide an integrated overview of the topic at hand. As a whole, this volume is designed to provide a broad portrait of goal research as it has been and is currently being conducted in the social psychological literature. It serves as an introduction to essential issues, while at the same time offering a sampling of cutting-edge research on core topics in the study of goal-directed behavior, such as how goals are represented, where goals come from, and what goals do in the process of regulation. -- Book Description.
Includes bibliographical references and index.
Keywords: Intentionalism; Goal (Psychology)